KEMAMPUAN BERPIKIR ALJABAR DALAM MENYELESAIKAN SOAL MATERI TEOREMA PHYTAGORAS - Avivah Aulia; Mohamad Rif'at; Dwi Astuti (UNIVERSITAS TANJUNGPURA, 2021)
This research aims to determine the algebraic thinking skills of students in solving questions on the subject of the Pythagorean theorem in students of SMP Negeri 19 Pontianak. The research method used is descriptive method in the form of case studies. The subjects in this study were six students and the object in this study was the ability to think algebraically in solving problems on the subject of the Pythagorean theorem. The data collection techniques used were test and non-test (interview). In this research, there is one student who achieves generational activities, two students in transformational activities and one student in global meta-level activities. In general, it can be concluded that the ability to think algebra in solving the problem of the Pythagorean theorem in SMP Negeri 19 Pontianak is that students are in transformational activities even though in generational activities students do not entirely write algebraic forms and equations. Students also have not been able to solve problems by writing down the rules used at each step, and not writing conclusions. Keywords : Algebraic Thinking Skills, Solve The Problem, Pythagorean Theorem